2021
DOI: 10.3389/fonc.2021.582040
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Autophagy-Related Genes and lncRNAs in Therapy and Prognosis of Colorectal Cancer

Abstract: Cellular autophagy plays an important role in the occurrence and development of colorectal cancer (CRC). Whether autophagy-related genes and lncRNAs can be used as ideal markers in CRC is still controversial. The purpose of this study is to identify novel treatment and prognosis markers of CRC. We downloaded transcription and clinical data of CRC from the GEO (GSE40967, GSE12954, GSE17536) and TCGA database, screened for differentially autophagy-related genes (DEAGs) and lncRNAs, constructed prognostic model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Furthermore, our study showed that the abundance of TIICs, such as T cells, resting memory CD4 T cells, and activated mast cells, was lower in the low-risk group compared with the high-risk group. These results are consistent with the results of Yang et al [ 53 ]. Besides, our study showed that the abundance of TIICs, such as resting memory CD4 T cells and activated mast cells, was lower in the low-risk score group compared with the high-risk group.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, our study showed that the abundance of TIICs, such as T cells, resting memory CD4 T cells, and activated mast cells, was lower in the low-risk group compared with the high-risk group. These results are consistent with the results of Yang et al [ 53 ]. Besides, our study showed that the abundance of TIICs, such as resting memory CD4 T cells and activated mast cells, was lower in the low-risk score group compared with the high-risk group.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, according to the risk score formula, patients were divided into the low-risk group and high-risk group by the median risk score. Similar to the previous studies ( Fan, Tian, 2020 ; Yang et al, 2021 ), the K-M curve showed that low-risk group survival was longer than the high-risk group with significance ( p < 0.05). The AUCs at 1-, 3-, and 5-years were 0.72, 0.814, and 0.83, which indicate that the predictive ability of the risk score signatured by autophagy-related lncRNAs were stable and the risk score can be set as an independent prognostic indicator.…”
Section: Discussionsupporting
confidence: 88%
“…In detail, the IRLncSig and age were treated as continuous variables, while the pathologic stage was coded as binary, "Stage I/II" and "Stage III/IV". We also compared the IRLncSig with four published prognostic signatures in CRC: a 15gene signature derived from Yang's study (Yang et al, 2021), a 6-lncRNA signature derived from Li's study (Li et al, 2020), a 6gene signature derived from Dai's study (Dai et al, 2020), and a 7-gene signature derived from Lu's study (Lu et al, 2021).…”
Section: Performance Comparison Of the Irlncsig With Other Clinical V...mentioning
confidence: 99%
“…We compared the IRLncSig with four recently published prognostic signatures in CRC: a 15-gene signature derived from Yang's study (Yang et al, 2021), a 6-lncRNA signature derived from Li's study (Li et al, 2020), a 6-gene signature derived from Dai's study (Dai et al, 2020), and a 7-gene signature derived from Lu's study (Lu et al, 2021). The results showed that the AUC values at 1-year, 3-years and 5-years were 0.78, 0.78 and 0.79, respectively, which were all higher than those of the other four signatures (Figure 9).…”
Section: Performance Comparison Of the Irlncsig With Other Clinical V...mentioning
confidence: 99%